Clinical profile and drug therapy of outpatients with arterial hypertension - N. V. Izmozherova; A. A. Popov; V. M. Bakhtin; M. A. Shambatov (Столичная издательская компания, 2020)
Aim. To study clinical profile and antihypertensive treatment features in outpatients observed in ambulatory facilities.Material and methods. 140 arterial hypertension (AH) outpatients were examined, questioning and anthropometry were performed. Blood pressure (BP) was measured on both hands, then twice on the hand with larger value, the medium value was calculated. Tests results were obtained from outpatient cards.Results. The sampling included 100 (71.4%) females and 40 (28.6%) males. Median of systolic BP at first measurement was 140.0 mm Hg (130.0;150.0), mean value of three BP measurements was 138.0 mm Hg (127.0;150.0) (p<0.001); median diastolic BP at first measurement was 83.0 mm Hg (80.0;90.0), mean BP value was 82.0 mm Hg (78.0;88.0) (p<0.001). Grade 1 AH was identified in 11.4% of patients, Grade 2 - in 35.7%, Grade 3 in 52.9%. No target organ damage was found in 26.4% of AH patients, asymptomatic target organ damage was diagnosed in 26.4%, and 61.4% had associated clinical conditions. Cardiovascular event risk was assessed as moderate in 13.6%, high - in 24.3% and very high - in 62.1% of patients. Every third patient had myocardial hypertrophy signs; Cornell index was detected more often than Sokolov-Layon index (p=0.006). Chronic kidney disease was diagnosed in 65.1% of patients: 44.0% of them had stage C2, 13.8% - stage C3A, 6.5% - stage C3B, and 1.8% - stage C4. 97.9% of AH patients received antihypertensive treatment. Daily medication consumption was reported by 127 people, and 10 patients reported taking medication as needed. Monotherapy was prescribed in 14.3% of patients; combined treatment was performed in 83.6% people. BP target value was achieved in 59 patients (42.1%) at first measurement results and in 71 (50.7%) ones at calculated mean value (p=0.002). Indications for statin use were identified in 86.4% of patients. Statins were administered in 56.2% patients having indications and in 21.1% of subjects without indications (p=0.006). Indications for antiplatelet therapy use were identified in 56.4% of patients. Antiplatelet treatment was administered in 58.2% of patients with indications and in 23.0% of subjects without indications (p<0.001).Conclusion. Glomerular filtration rate and left ventricular myocardial hypertrophy amplitude criteria calculation allow to diagnose subclinical target organ damage in outpatients at physician visit without additional costs. Compliance with the current antihypertensive therapy guidelines allows to achieve target BP in current practice. Compliance with the BP measuring rules allows to adequately assess the effectiveness of antihypertensive therapy. A significant proportion of AH outpatients have a very high cardiovascular risk, which requires lipid-lowering and antiplatelet therapy.